THE EFFECT OF TASK-BASED LANGUAGE TEACHING ON SPEAKING FLUENCY OF A2 LEARNERS - Umarova Dilshoda (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study investigates the effectiveness of Task-Based Language Teaching (TBLT) in improving the speaking fluency of A2-level English learners. Speaking fluency remains a major challenge for learners at lower proficiency levels due to limited vocabulary, lack of confidence, and insufficient communicative practice. This research adopts a quasi-experimental design involving pre- and post-tests to measure learners’ fluency development after implementing task-based instruction. The findings demonstrate that TBLT significantly enhances learners’ speaking fluency by increasing speech rate, reducing pauses, and improving communicative confidence. The study highlights the importance of meaningful interaction and real-life tasks in developing oral proficiency. Implications for English language teaching and classroom practices are discussed.